SKRINING AWAL ANTITUMOR MELALUI PENDEKATAN UJI TOKSISITAS KANDUNGAN SENYAWA DALAM EKSTRAK n-HEKSANA RIMPANG TEMU PUTIH (Curcuma zedoaria (Berg.) Roscoe) - Susanah Rita, Wiwik; Gede Bawa, I G. A.; Lilis Wirastiningsih, Ni Luh Putu (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 1 Januari 2012, 2012)
Isolation and identification of cytotoxic compounds from n-hexane extract of white turmeric rhizomes (Curcuma zedoaria (Berg.) Roscoe) has been performed. Extraction was done by maceration technique. Saponification reaction was applied to separate the fat with another lipid, separation and purification was then performed by chromatographic techniques. Toxicity tests performed by the method of Brine Shrimp Lethality Test (BSLT) using Artemia salina L. larvae, while the analysis of the most toxic isolates were performed by Gas Chromatography-Mass Spectroscopy (GC-MS). Extraction of 1700 g of dried white turmeric rhizome powder produced 39.68 g of concentrated n-hexane extracts. The results of toxicity tests with n-hexane extract of Artemia salina L. larvae was obtained LC50 values of 79.43 ppm. Saponification of n-hexane extract produced 9.18 g of n-hexane phase and 137.38 g water phase. Toxicity test indicated that n-hexane extract phase was the most toxic with the LC50 of 17.78 ppm. Then the active phase was separated and purified by gradient column chromatography and obtained 11 fractions. Fraction 11 was the the most toxic with the LC50 of 3.8 ppm. The column chromatography obtained two fractions (F11a and F11b), which F11b was the most active with LC50 of 3.5 ppm. The analysis of isolate by Gas Chromatography Mass Spectroscopy showed a mixture of compounds: tetradecane, hexadecane, 3-methylheptadecane, octadecane, 2-methyleicosane, n-docosane, and heneicosane.
Keywords: Toxicity, White Turmeric, Curcuma zedoaria (Berg.) Roscoe, Artemia salina L